KOMPETENSI MANAJERIAL KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU PADA MASA PANDEMI COVID-19 - Ismail Ridwan (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2020)
This study aims to determine the teacher performance improvement program during the Covid-19 pandemic, the implementation of the teacher performance improvement program during the Covid-19 pandemic, and the supervision of teacher performance improvement programs during the Covid-19 pandemic. This research uses a qualitative approach with descriptive methods. Data collection techniques are carried out through observation, interviews, and documentation study. The subjects of this study were the head of the madrasah, the deputy head of the madrasah in the field of curriculum, and teachers of MTs Negeri 1 Pangandaran. The results showed: 1) The principal of the madrasah program and its implementation were appropriate and implemented. The principal of madrasas in improving teacher performance during the Covid-19 pandemic is through e-learning training programs for teachers, online education seminars, workshops, Subject Teacher Deliberation (MGMP), Counseling Guidance Teacher Deliberation (MGBK), giving awards to outstanding teachers, providing additional credit to teachers to carry out online learning, as well as lending IT devices in the form of laptops to teachers for the learning process, 2) Supervision of madrasah principals in improving teacher performance during the Covid-19 pandemic was carried out continuously through two-way communication with teachers, visits class with notification and also without notification via e-learning, individual communication via WhatsApp or telephone messages, and inviting supervisors to madrasas to evaluate teacher performance improvement programs during the Covid-19 pandemic.